Impact of Ascending to Descending Aortic Bypass for Aortic Coarctation on 3-Dimensional Hemodynamics. Issue 11 (17th March 2015) - Chowdhary, Varun; Rose, Michael; Murtagh, Gillian; Schnell, Susanne; Barker, Alex; Russell, Hyde; Markl, Michael; Carr, James
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.